Efeito da adição de alumina nas propriedades químicas e mecânicas de biocerâmicas de apatitas nanométricas sintetizadas via sol-gel - Costa, Claudia de Matos (2014)
The need for obtaining new materials to replace human body parts that were destroyed or damaged led scientists from different research areas of new materials used for implants Calcium phosphate when crystallized in the form of hydroxyapatite [Ca10 (PO4)6 (OH)2 ] is a bioactive and biocompatible ceramics primarily similar to natural bone and teeth ratio This workaims to produce nanometrics apatite bioceramics via sol - gel, get composites based on hydroxyapatite and alumina materials by varying the concentration of alumina and evaluate mechanical chemical physical properties and microstructure of the sintered samples The properties and characteristics of bioceramics were analyzed using the techniques of X-ray diffraction and infrared spectroscopy scanning electron microscopy (SEM particle size analysis test strength by diametrical compression pressed samples and bioactivity test From the results of X ray was it possible to identify the representative peaks in all samples corresponding to hydroxyapatite phase but also to aluminum phosphate aluminum calcium oxide and calcium oxide From in infrared analysis it was possible to identify the groups present in nanocompósitos Tensile strength obtained by diametrical compression on different compositions of nanocomposites showed that the percentage of alumina present influences the mechanical strength of the material